The paradox of modern suffering - Sørensen, Anders Dræby (Tidsskrift for Forskning i Sygdom og Samfund, 2010)
Since the end of the 18th century, many people in the developed Western countries have experienced an increase in housing conditions, income, security, health, and education levels as well as a progress in human rights and democratic values and institutions. These trends are often perceived as signs of a positive development towards a higher level of happiness and a lower level of suffering. Nevertheless commentators have pointed out how several studies and surveys seem to indicate that the levels of existential suffering and mental distress have not decreased in line with this political, economic, and social development The article introduces the thesis of the paradox of suffering in modern Western culture. The concept of this paradox designates how modern Western culture is centred on a pursuit of happiness and avoidance of suffering, but continuously involves widespread existential suffering and mental distress. Furthermore, the main point of the article is to demonstrate how the cultural pursuit of happiness, paradoxically, is what causes a lot of the present suffering.